MANAGING WORKPLACE DISCRIMINATION, HARASSMENT AND RETALIATION: AN ASSESSMENT OF KENYAN WORKPLACE - Ochieng, Olayo; Kamau, Lewis (International Journal of Law and Policy, 2021)
Purpose: This paper sought to examine whether workplace training in mitigating discrimination, harassment and retaliation has been effective. Methodology: This study adopted exploratory research methodology. Exploratory research design is used to investigate a problem which is not clearly defined. It is conducted to have a better understanding of the existing problem, but will not provide conclusive results. It explored studies conducted on the topic. This means that the study relied on desk-top review of the existing studies and documented case laws. Further, it relied on the cases laws. A narrative analysis was done and at this point the information was interpreted by comparing the findings with the findings of other empirical studies. This information was interpreted together with the "˜Stories within stories' and related to the existing literature Findings: The results found that while workplace training increases sensitivity, it is associated with less accuracy in detecting discrimination, harassment, and retaliation. This is based on the fact that there are many cases on the matter before the courts. Further, the study shows that there is no relationship between training and the ability of the manager to propose the required response after the act. Unique contribution to theory, practice and policy: The study recommends that there is need for organizations to develop action plans that will measure the effectiveness of trainings. There is need to regularly review policies to ensure that they are modern realities such as online harassment. Finally the study recommends amendment of the current employment Act to exclusively require that employers must conduct training on the issues.